2020
DOI: 10.11002/kjfp.2020.27.3.333
|View full text |Cite
|
Sign up to set email alerts
|

Quality characteristics and antioxidant activities of ganache added with Porphyra tenera powder

Abstract: The purpose of this study was to investigate the quality characteristics and antioxidant activities of ganache added with Porphyra tenera powder (PTP). The levels of PTP addition to ganache were 0, 1, 2, and 3 wt%. The lightness (L) and yellowness (b) values of the ganache in the Hunter color system decreased upon increasing the amount of PTP. In addition, textural examinations showed that the hardness of the ganache increased upon PTP addition. Furthermore, sensory evaluations indicated that the overall accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…extra virgin olive oil, the ABTS experiment showed that it had antioxidant properties (Giuffrè et al, 2018;Giuffrè et al, 2019;Valencia-Cordova et al, 2021). In addition, as a result of an experiment using a substance similar to this study, it was confirmed that the ABTS activity increased significantly as the amount of laver added increased (Hwang and Tai, 2014;Park et al, 2020). Therefore, this experiment of P. tenera Jeolpyeon was confirmed to have antioxidant function.…”
Section: Analysis Of Total Phenol and Flavonoid Contents In Jeolpyeon...supporting
confidence: 76%
See 3 more Smart Citations
“…extra virgin olive oil, the ABTS experiment showed that it had antioxidant properties (Giuffrè et al, 2018;Giuffrè et al, 2019;Valencia-Cordova et al, 2021). In addition, as a result of an experiment using a substance similar to this study, it was confirmed that the ABTS activity increased significantly as the amount of laver added increased (Hwang and Tai, 2014;Park et al, 2020). Therefore, this experiment of P. tenera Jeolpyeon was confirmed to have antioxidant function.…”
Section: Analysis Of Total Phenol and Flavonoid Contents In Jeolpyeon...supporting
confidence: 76%
“…Red seaweeds including Laver are reported to be rich in phenolic compounds such as catechin, phlorotanin, and fucoxanthin, confirming their antioxidant activity (Yan et al, 1996;Yan et al, 1999;Ganesan et al, 2008). In addition, it was confirmed that the total polyphenols and flavonoids were significantly increased in the study of cookies and ganache by adding the same substances as in this experiment (Hwang and Tai, 2014;Park et al, 2020). Therefore, the total phenol content and flavonoids in this experiment were confirmed to have antioxidant function, suggesting that they are closely related.…”
Section: Analysis Of Total Phenol and Flavonoid Contents In Jeolpyeon...supporting
confidence: 71%
See 2 more Smart Citations
“…Previous studies have studied the incorporation of mulberry leaf, black seed oil, aronia, and Porphyra tenera seaweed into chocolate ganache [10][11][12][13]. However, there has been no study on the effect of adding edible flowers, namely butterfly pea and roselle on white chocolate ganache.…”
Section: Introductionmentioning
confidence: 99%